A Retrospective Analysis of Clinical Utilization Between Patients Who Used Telemedicine and Office Visits in Outpatient Physical Medicine and Rehabilitation Clinics During the COVID-19 Pandemic. (12th January 2023) - Gilmer, Gabrielle; Jackson, Natalie; Koscumb, Stephen; Marroquin, Oscar C.; Sowa, Gwendolyn
Abstract : Objective: To describe the demographic characteristics of patients who used telemedicine and office visits in physical medicine and rehabilitation during the COVID-19 pandemic and to quantify differences in clinical utilization between groups. Clinical utilization was defined as emergency department, urgent care, and hospital visits. Design: This was a retrospective cohort study of 1096 patients who used telemedicine and 1171 patients who used office visits from April to June 2020 in the outpatient physical medicine and rehabilitation clinics at University of Pittsburgh Medical Center for musculoskeletal-related complaints. Results: The telemedicine groups contained proportionally more people of color and higher comorbidities than the office visit groups. Patients who were seen in the telemedicine groups were more likely to be prescribed opioids than the office visit group. There were no differences in clinical utilizations between the telemedicine and office visit groups. Conclusions: The higher use of telemedicine in patients of color suggests a need for studying long-term outcomes to evaluate differences in care standards. There is an urgent need to understand how telemedicine affects opioid prescribing practices. Lastly, future studies are needed to understand why there were no differences in clinical utilization between the telemedicine and office visit groups.